2020
DOI: 10.3390/antibiotics9080524
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenic Role of Actinomyces spp. and Related Organisms in Genitourinary Infections: Discoveries in the New, Modern Diagnostic Era

Abstract: Actinomycosis is a chronic, suppurative, granulomatous infectious disease, caused by different species of Actinomyces bacteria. To date, 26 validly published Actinomyces species have been described as part of a normal human microbiota or from human clinical specimens. Due to the rapid spread of new, modern diagnostic procedures, 13 of 26 of these species have been described in this century and the Actinomycetaceae family has undergone several taxonomic revisions, including the introduction of many novel specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 150 publications
(302 reference statements)
1
17
1
1
Order By: Relevance
“… 20 , 21 Other rare pathogenic microorganisms, such as anaerobes, Actinomyces and Actinomyces -like organisms (ALOs), had distributed in various ages of male genitourinary infection. 6 , 22 In our study, the proportion of patients under 35 years old was 18.2% (4 cases all had cUTIs), which was higher than expectation. This might suggest a trend to the demographic change in severe male genitourinary infection.…”
Section: Discussioncontrasting
confidence: 62%
“… 20 , 21 Other rare pathogenic microorganisms, such as anaerobes, Actinomyces and Actinomyces -like organisms (ALOs), had distributed in various ages of male genitourinary infection. 6 , 22 In our study, the proportion of patients under 35 years old was 18.2% (4 cases all had cUTIs), which was higher than expectation. This might suggest a trend to the demographic change in severe male genitourinary infection.…”
Section: Discussioncontrasting
confidence: 62%
“…Dysbiosis of the gut microbiome has also been associated with many cancers ( 8 , 14 16 ), including LC ( 8 ). A previous study suggested an increase in Enterococcus in the stool of LC patients compared to that of healthy subjects and a decrease in Bifidobacterium and Actinobacteria ( 6 ), of which others have shown that the response to immunotherapy in NSCLC patients is associated with specific changes of individual species, such as Alistipes putredinis , Bifidobacterium longum , and Prevotella copri as well as the overall diversity of the gut microbiome ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic feature of infections caused by microorganisms of the order Actinomycetales is a chronic disease, granulomatous (nocardiosis and rhodococcosis) or pyogranulomatous (actinomycosis) process in a macroorganism leading to formation of abscesses and fibrosis in various organs and tissues (Gajdács & Urbán, 2020). Animals rarely recover without an appropriate therapy.…”
Section: Introductionmentioning
confidence: 99%